PsycEXTRA Dataset 1973
DOI: 10.1037/e538442008-001
|View full text |Cite
|
Sign up to set email alerts
|

A factor analytic study of attritions from Naval aviation training

Abstract: Wife tllihapIJy with ily flying 113 Unable to perforl wedl while flying the aircraft 75 D)o not like obedience and discipline initilled by fear orlentidon 54 54 Extremne apprehension when anticipating upcoming ifighta or during the flight 76 I)igsatisfied with pipeline amigliuent 42 4t1 Did not like flying 35 65 49 lo not like military discipline 84

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We note that the 20-item motivation scale utilized to derive the aforementioned factors was originally developed for a combined study of NFOs and pilots (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the 20-item motivation scale utilized to derive the aforementioned factors was originally developed for a combined study of NFOs and pilots (5).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study (5) has shown that NFOs are dissatisfied with pipeline assignment. In fact, dissatisfaction is the third most influential reason for attrition from the NFO training program (3).…”
Section: Introductionmentioning
confidence: 99%